Implementasi Penguatan Karakter Toleransi Beragama di Pesantren Indonesia - Abdul Hadi; Kusik Kusuma Bangsa (Jurnal Pendidikan Indonesia, 2025)
This consider points to analyze the usage of reinforcing devout resilience character in Indonesian pesantren, considering the significant part of pesantren as Islamic instructive teach in forming the states of mind and behavior of understudies. The investigate is persuaded by the challenges of pluralism in Indonesia, which requests expanded devout resilience, especially among the more youthful era. The think about utilizes a quantitative approach with a overview strategy including 500 respondents from 10 pesantren in different locales. Information was collected employing a survey with a Likert scale and tried for legitimacy and unwavering quality.The comes about appear that 85% of understudies get it the significance of devout resistance as portion of Islamic lessons. Besides, 75% of pesantren have consolidated resilience instruction into their educational module, both through formal classes and extracurricular exercises. In any case, 20% of understudies hold select sees toward other religions, showing a require for advance fortification. Furthermore, 60% of pesantren instructors expressed that they require extra preparing to viably educate devout resistance values. In conclusion, the think about demonstrates that endeavors to fortify the character of devout resistance in Indonesian pesantren have been fruitful, but there’s still room for advancement, especially in educator preparing and experiential learning. The proposed proposals incorporate creating more comprehensive resistance instruction modules and giving more seriously educator preparing to guarantee that pesantren can contribute maximally to building a tolerant and concordant society in Indonesia.